Symptoms and sleep characteristics of tic disorder children with allergic diseases: a case–control study - Panpan, Zhang; Yang, Liu; Na, Wang; Tao, Ma; Jinyuan, Wang; Guixiang, Zhang; Yifan, Cui (Frontiers in Pediatrics, 2025)
IntroductionRecent studies have shown a close relationship between tic disorder (TD) and allergic diseases in children. Allergic diseases also have a significant impact on children's sleep. Regrettably, it remains unclear whether TD children with comorbid allergic diseases exhibit distinct symptoms and sleep characteristics.ObjectiveThis study aimed to explore the symptoms and sleep characteristics of TD children with allergic diseases.MethodsThis was a case–control study involving 242 TD children (aged 3–14 years), of whom 168 had allergic diseases and 74 did not have allergic diseases. General information and allergy histories were recorded for all participants. The Yale Global Tic Severity Scale (YGTSS) was used to assess TD symptoms. All guardians of TD children were required to complete the Children's Sleep Habits Questionnaire (CSHQ).ResultsCompared with the group of TD children without allergic diseases, the comorbid allergic disease group had significantly higher impairment scale scores and total tic scores on the YGTSS (all p < 0.05). Parasomnias score, sleep-disordered breathing score, and CSHQ total score were also significantly higher in the TD group with combined allergic diseases (all p < 0.05). Further analyses revealed no significant difference in TD symptoms and sleep between groups based on the number of allergic diseases and control of allergic diseases (all p > 0.05). However, significant differences in TD symptoms and sleep occurred based on the type of allergic disease. Among them, the impairment scale score, total tic score, and sleep-disordered breathing score of the allergic rhinitis group were significantly increased (all p < 0.05); in the allergic conjunctivitis group, the total motor score and total tic score increased significantly, and the daytime sleepiness score decreased significantly (all p < 0.05). In addition, we found a correlation between the YGTSS and CSHQ scores.ConclusionThis study found that TD children with allergic diseases exhibited more severe clinical symptoms and higher CSHQ total scores. The clinical and sleep changes are particularly significant in TD children with different types of allergic diseases, especially allergic rhinitis and allergic conjunctivitis.